الحداثــة ومنظــــُومـــة الاستعمـــار الاستيطــــاني تفكيك بُنيوي للإطـار العــــــام - مُسلًــــم, نديـــم (revue mofakir, 2018)
شهدت المجتمعات الإنسانية في القرون الخمسة السابقة ظهور وترسّخ النظام الرأسمالي ، كبناء اقتصادي ضخم ومتشعب مُترسخاً عام بعد عام ، ومُرسخاً معه منظومات سياسية وثقافية ومعرفية خاصة به . وكانت الحداثة هي الإطار الجامع لمنظومات البناء الفوقي المتفرعة عن النظام الرأسمالي ، حيث تدعم في مجالاتها خاصية التوسع الاستثماري الاقتصادي للرأسمالية . وتــُعتبر قارة أوروبا مهد النظام الرأسمالي ، فيها نشأ ومنها توسع خارجاً ، مُعتمدا كرأس حربة في منظومة توسعه الربحية في العالم بأسره خارج قارة أوروبا على منظومة الاستعمار الاستيطاني ، والتي أسست بدورها لمنظومة الهيمنة المعاصرة . تمّ تبنّي منظومة الحداثة في أوروبا بعد انهيار عصر الإقطاع ، كإطار جامع للبناءات والتشكيلات الاجتماعية والثقافية والعلمية فيها ، وهكذا كان للحداثة والاستعمار الاستيطاني علاقات بنيوية بينية وطيدة ببعض منذ تشكلهما ، كونهما يعملان وظيفيا معاً في خدمة نفس المشروع الذي أوجدهما أصلاً ، علاقات تهدف لتثبيت أركان أنماط الإنتاج الرأسمالي المتراكمة ، من الماركنتلية التجارية ثم الرأسمالية الصناعية ، فالرأسمالية المالية تباعاً ، ضمن خاصية التوسع الملازمة لهذه الأنماط في العصر الحديث . فعند إجراء تفكيك بنيوي للإطار العام الشامل للحداثة والاستعمار الاستيطاني ، يتضح أنهما منظومتين وظيفتين لا غاية في حدّ في ذاتهما ، وأن الأهداف الخاصة بهما يتم رسمها في قلب الفواعل المهيمنة على النظام الرأسمالي ووفق غاياته الربحية التوسعية ، وأيُّ عكس لفهم هذه النقطة الجوهرية ( كما يقع فيه الكثير ، من اعتبار الحداثة على وجه الخصوص هدفا قائما بذاته ) يؤدي حتما إلى نتائج خاطئة ومقلوبة رأسا على عقب .   Abstract :    Human societies have seen the emergence in the previous five centuries an entrenched capitalist system, such as a huge economic structure and entrenched year after year, and enhancing a political, cultural and knowledge systems of its own. The modernity is the overarching framework for systems superstructure is a subsidiary of the capitalist system, which supports investment in the fields of economic expansion of capitalism property. The continent of Europe, the cradle of the capitalist system, which grew out of it and expanded, depending spearhead its expansion in profitability in the whole world outside the continent of Europe the system colonial settlement system, which established in its turn the system of contemporary dominance.     The adoption of modern system in Europe after the collapse of the era of feudalism, as a framework for its social, cultural and scientific structures, and so was the recent settlement and colonization structural relationships close in its shaping, since its working and functioning in the same project, which was originally its source, relations aims to install pillars patterns accumulated capitalist production, the mercenary of commercial and industrial capitalism, financial capitalism, respectively, within the expansion inherent in these patterns in the modern era property. When action to dismantle structural framework Comprehensive General of the modern settlement and colonialism, it is clear they have two systems and two not very much in themselves, and that their own objectives are drawn in the heart of actors function dominant capitalist system and in accordance with the objectives of profitability expansion, and any reversal to understand this fundamental point (as it is located many, of modernity considered particularly target freestanding) inevitably leads to wrong and contradictory results.